Dynamic Investment and Financing under Personal Taxation - Morellec, Erwan; Schürhoff, Norman (Review of Financial Studies, 2010)
[In this paper we examine the effects of capital gains taxation on firms' investment and financing decisions. We develop a real-options model in which the timing of investment, the decision to default, and the firm's capital structure are endogenously and jointly determined. Our analysis demonstrates that the asymmetric taxation of capital gains and losses fosters investment by eroding the option value of waiting. It also shows that firms controlled by taxable investors employ more equity financing, the higher the firm's stock price and the worse the firm's historical performance. Using a large sample of U.S. industrial firms that are owned by taxable investors between 1970 and 2008, we present new evidence on corporate investment and financing policies, which is supportive of the model's predictions.]